Daily Profit Analysis: Daily Productivity Scheduling with Multiple Linear Regression - Putra, Fredi Ganda; Syazali, Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2020)
The purpose of this study was to see which day factors (Monday, Tuesday, Wednesday, Thursday, Friday, Saturday, Sunday) had the greatest impact on the net income of a store. The method used is a quantitative method using multiple linear analysis. The results show that Monday is the most influential on profits